ANALYSIS OF JOB TRAINING AND JOB QUALITY ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE LOYALTY AT THE SOLOK BRANCH BPJS KETENAGAKERJAAN OFFICE - Arya Chandra Gusnanto; Mesra B (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this research is to find out the results of research on the influence of Job Training and Work Quality on Employee Performance through Employee Loyalty with associative quantitative research. This research was carried out at the Solok Branch of the BPJS Employment Office, and the population of this research was 40 employees, the sample used was a saturated sample. because the researcher made the entire population into a sample, the data source used was a primary data source, to collect data the researcher distributed questionnaires and surveys. This research model uses analytical skills, and the measuring tool uses Sem PLS version 3. The results of this research are that work quality has a positive and insignificant effect on employee performance. Work Quality has a positive and significant effect on Work Loyalty. Employee loyalty has a positive and significant effect on employee performance. Job Training has an insignificant negative effect on Employee Performance. Job Training has a positive and significant effect on Job Loyalty. Work Quality has a positive and significant effect on Employee Performance through Loyalty. Job Training has a positive and insignificant effect on Employee Performance through Job Loyalty.